HEGEMONIC AND MINORITY DISCOURSES AROUND IMMIGRANTS: A CORPUS-BASED CRITICAL DISCOURSE ANALYSIS - Al Fajri, Muchamad Sholakhuddin (Indonesian Journal of Applied Linguistics, 2017)
This study aims to analyse discourses surrounding the word immigrants in a large collection of naturally occurring language, ‘ukWac’ corpus (Web as Corpus). It employs corpus linguistics as a methodology to carry out critical discourse analysis research. Specifically, collocation analyses were used to identify dominant representations and discourse prosodies (Stubbs, 2007) of immigrants. Concordance analyses were then applied to examine the data in a more qualitative way. The findings suggest that while there are a few instances indicating positive representations of immigrants, hegemonic discourses around them are more negative. They are predominantly constructed as illegal entities, victims and dangerous groups. These constructions are likely to prime people to think that all immigrants are illegal and threatening, and will not be able to integrate into their host society.